Psychosocial strain and coping of Finnish working mothers during the COVID-19 lockdown: a job demand-control approach - Venla Panula; Nelli Lyyra; Angeliki Kallitsoglou; Emmanuel Acquah; Pamela-Zoe Topalli (Frontiers Media S.A., 2024)
IntroductionIn March 2020 many countries around the world, including Finland, implemented lockdown measures to mitigate the unprecedented impacts of the coronavirus infectious disease (COVID-19) on public health. As a result, school and daycare settings closed indefinitely and working from home became the new normal for a big part of the workforce, which came with increased homeschooling and childcare responsibility for mothers.MethodsIn this article we present the findings from maternal responses to open ended questions on psychosocial well-being, and experiences of combining work, family life and homeschooling during the COVID-19 national lockdown in Finland in March-May 2020. Working mothers' responses (n = 72) were analyzed through the lens of Karasek's job demand-control model, focusing on how the mothers experienced the demands of their life during the lockdown, and how they saw their possibilities to control the situation.ResultsThe findings indicated important variation in the level of experienced demand and control and associated compensatory factors during the COVID-19 lockdown across different subgroups of working mothers.DiscussionThe findings have implications for understanding strain and plausible supports among working mothers during the COVID-19 lockdown as well as in the face of acute adversity including the next possible public health crisis.